Analysis Of Sustainability Communication Strategies in PT. Jaya Ancol People's School CSR Program - Aprilia; Shofura Afifah; Wulan Furrie (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to analyze the Communication Strategy for Sustainability of the PT People's School CSR Program. Jaya Ancol with a focus on program objectives, communication methods used, and the impact that has been produced. The research method used is a literature study by collecting and analyzing secondary data related to CSR programs and corporate sustainability communications. The analysis results show that PT. Jaya Ancol has succeeded in conveying sustainability messages through various communication channels, strengthening public awareness, and building support for the company's sustainability efforts. In addition, the Sekolah Rakyat CSR Program provides concrete benefits in the form of increasing access to education for the community around Ancol and strengthening positive relationships between the company and the local community. Continuous evaluation and responsiveness to change are the keys to maintaining the sustainability of this program. This study provides a positive picture of the importance of strategic communications and CSR programs in achieving corporate sustainability goals